2018
DOI: 10.1063/1.5037925
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-terminated polycrystalline diamond MOSFETs with Al2O3 passivation layers grown by atomic layer deposition at different temperatures

Abstract: Metal oxide semiconductor field effect transistors (MOSFETs) with Al2O3 passivation layer grown by atomic layer deposition (ALD) at 200 oC and 300 oC were fabricated on hydrogen-terminated polycrystalline diamond by using gold mask technology. The device with 200 oC grown Al2O3 dielectric shows high output current, low on-resistance, large threshold voltage and high transconductance compared to that with 300 oC grown Al2O3. A maximum drain current of 339 mA/mm has been achieved by the 2-μm device of the former… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…We first observe that, prior to passivating samples A and B, the sheet densities are significantly higher than their passivated counterparts (A' and B'). As reported in other works, a drop in the sheet density after the deposition of Al 2 O 3 is common [4,35], which is attributed to the lower density of surface acceptors in Al 2 O 3 in comparison to air-adsorbates. It is also shown in Fig.…”
Section: Resultssupporting
confidence: 63%
“…We first observe that, prior to passivating samples A and B, the sheet densities are significantly higher than their passivated counterparts (A' and B'). As reported in other works, a drop in the sheet density after the deposition of Al 2 O 3 is common [4,35], which is attributed to the lower density of surface acceptors in Al 2 O 3 in comparison to air-adsorbates. It is also shown in Fig.…”
Section: Resultssupporting
confidence: 63%
“…In this work, we focused on the monolithic integration method to fabricate a polycrystalline (PC) diamond hole FET and AlGaN/GaN HEMT simultaneously on a single chip to deliver a complementary inverter for high-temperature. Previous work showing that PC diamond hole FET using a PC diamond plate (Element six TM200) with an average grain size between 80 and 100 μm demonstrates comparable performance to the SC diamond hole FET in recent works, pointing to the validity of our approach. In a separate study, the role of PC diamond as a heat spreader was also discussed, making this combination even more desirable for various applications .…”
Section: Introductionmentioning
confidence: 56%
“…Devices fabricated at 200 °C displayed a higher output current, larger V T , and lower onresistance compared with that deposited at 300 °C. [180] In addition, ALD-processed Al 2 O 3 has been also employed as an effective passivation layer to reduce the surface trap density, and thus suppress the threshold voltage hysteresis significantly. [80] Si et al demonstrated enhanced FET performances through the passivation of indium selenide (𝛼-In 2 Se 3 ) by ALD-Al 2 O 3 .…”
Section: Aluminum Oxidementioning
confidence: 99%